If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t(t + -5) = 34 Reorder the terms: t(-5 + t) = 34 (-5 * t + t * t) = 34 (-5t + t2) = 34 Solving -5t + t2 = 34 Solving for variable 't'. Reorder the terms: -34 + -5t + t2 = 34 + -34 Combine like terms: 34 + -34 = 0 -34 + -5t + t2 = 0 Begin completing the square. Move the constant term to the right: Add '34' to each side of the equation. -34 + -5t + 34 + t2 = 0 + 34 Reorder the terms: -34 + 34 + -5t + t2 = 0 + 34 Combine like terms: -34 + 34 = 0 0 + -5t + t2 = 0 + 34 -5t + t2 = 0 + 34 Combine like terms: 0 + 34 = 34 -5t + t2 = 34 The t term is -5t. Take half its coefficient (-2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. -5t + 6.25 + t2 = 34 + 6.25 Reorder the terms: 6.25 + -5t + t2 = 34 + 6.25 Combine like terms: 34 + 6.25 = 40.25 6.25 + -5t + t2 = 40.25 Factor a perfect square on the left side: (t + -2.5)(t + -2.5) = 40.25 Calculate the square root of the right side: 6.34428877 Break this problem into two subproblems by setting (t + -2.5) equal to 6.34428877 and -6.34428877.Subproblem 1
t + -2.5 = 6.34428877 Simplifying t + -2.5 = 6.34428877 Reorder the terms: -2.5 + t = 6.34428877 Solving -2.5 + t = 6.34428877 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + t = 6.34428877 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + t = 6.34428877 + 2.5 t = 6.34428877 + 2.5 Combine like terms: 6.34428877 + 2.5 = 8.84428877 t = 8.84428877 Simplifying t = 8.84428877Subproblem 2
t + -2.5 = -6.34428877 Simplifying t + -2.5 = -6.34428877 Reorder the terms: -2.5 + t = -6.34428877 Solving -2.5 + t = -6.34428877 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + t = -6.34428877 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + t = -6.34428877 + 2.5 t = -6.34428877 + 2.5 Combine like terms: -6.34428877 + 2.5 = -3.84428877 t = -3.84428877 Simplifying t = -3.84428877Solution
The solution to the problem is based on the solutions from the subproblems. t = {8.84428877, -3.84428877}
| 9x^2=-9x-2 | | -2c+4-5c=-29 | | -12+6x=24 | | 230.00+0.15p=344.00 | | -4(2x-1)=3(5x-1)+7 | | 2(a-4)=-2 | | 7p+13=8 | | 7p+p-5p-3=15 | | 2x-4=10-60 | | 6(x+6)-5=37-2x-6+8x | | 4(2x-5)=-2x+5 | | 7(7x+5)=49x-1 | | 7-z=10 | | -3+7(x-4)=12x+6-5x | | -19=5+6x | | 7+7-(-2x)+3= | | z+11=-1 | | 8-9y=11 | | 6x+1.5-0.8x=0.7x-8.4 | | 0.4x-0.1(3-5x)=-0.5(x-5) | | 9e=108 | | 12+6c=96 | | 16=5-n | | 18+6z=-3 | | 9e-12=96 | | 2(4-3x)=-16 | | -2(x+5)+5=6(x+2)+9 | | 3a=5a+6 | | 18z+6z=-3 | | 13t+-2t=11 | | (1/3)(y+11)=3y-5(y-4) | | 2(t-2)=26 |